2012
DOI: 10.1158/1535-7163.mct-11-0979
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pan-Histone Deacetylase Inhibitor and Autophagy Inhibitor Exerts Superior Efficacy against Triple-Negative Human Breast Cancer Cells

Abstract: Histone deacetylase (HDAC) inhibitors (HDI) induce endoplasmic reticulum (ER) stress and apoptosis, while promoting autophagy, which promotes cancer cell survival when apoptosis is compromised. Here, we determined the in vitro and in vivo activity of the combination of the pan-HDI panobinostat and the autophagy inhibitor chloroquine against human estrogen/progesterone receptor and HER2 (triple)-negative breast cancer (TNBC) cells. Treatment of MB-231 and SUM159PT cells with panobinostat disrupted the hsp90/his… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 52 publications
4
85
1
3
Order By: Relevance
“…This abruption of the HSF1 from the multiprotein comlex is reported to lead to HSF1 phosphorylation, trimerization and nuclear translocation (125,126). Moreover, panobinostat treatment induced endoplasmic reticulum stress response and autophagy (123), evidence also supported by previous research (127)(128)(129). Combinational treatment of panobinostat with chloroquine was found to significantly enhance both the in vivo and the in vitro effect of panobinostat, given the fact that it inhibited tumor growth and increased viability of MDA-MB-231 xenografts (123).…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 70%
See 1 more Smart Citation
“…This abruption of the HSF1 from the multiprotein comlex is reported to lead to HSF1 phosphorylation, trimerization and nuclear translocation (125,126). Moreover, panobinostat treatment induced endoplasmic reticulum stress response and autophagy (123), evidence also supported by previous research (127)(128)(129). Combinational treatment of panobinostat with chloroquine was found to significantly enhance both the in vivo and the in vitro effect of panobinostat, given the fact that it inhibited tumor growth and increased viability of MDA-MB-231 xenografts (123).…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 70%
“…A study on MDA-MB-231cells investigated the in vitro and in vivo effect of co-treatment of panobinostat with the autophagy inhibitor chloroquine (123). First of all, panobinostat treatment disrupted the hsp90/HDAC6/HSF1/p97 complex (124,125) and induced a heat shock response mediated by heat shock factor protein 1 (HSF1).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…We and others have demonstrated that inhibition of autophagy leads to synergistic enhancement of the anticancer activity of HDAC inhibitors. 8,9,15,16,[19][20][21] These studies provided the foundation for the clinical evaluation of the autophagy inhibitor HCQ in combination with VOR as a potential novel therapy for advanced solid tumors. We selected 400 mg daily dosing for VOR in this study, which is frequently used for VOR administration.…”
Section: Discussionmentioning
confidence: 99%
“…In light of such evidence, we cannot exclude the occurrence of an interplay between the early ROS increase, MMP collapse, and autophagy down-regulation in JAHA-treated MDA-MB231 cells, although further studies will be required to confirm this hypothesis. Importantly, Rao et al 51 reported the superior anticancer activity of cotreating triple-negative breast cancer cells and xenografts with the pan-HDACi panobinostat and the autophagy inhibitor chloroquine; therefore, the possible clinical utilization of the sole JAHA, an HDACi possessing an intrinsic autophagy-inhibiting activity, appears to be worth investigating. Noteworthy, the time−course study of JAHA effect on the control of the autophagic flux revealed a biphasic trend of the biological progress, whose molecular basis will deserve further and more detailed investigation.…”
Section: ■ Discussionmentioning
confidence: 99%